INFLUENCE OF TERMS AND METHODS OF SOWING ON THE STRUCTURE OF SEED COENOSIS OF SOWING MILLET VARIETIES - Полторецький, С. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2015)
Despite considerable antiquity and a large number of studies on optimizing sowing millet, there is still no consensus on the characteristics of their establishing; considering climate changes in terms of regional studies clarifying terms and methods of sowing different millet varieties in seeding-down acquires particular relevance. In order to determine optimal terms and methods of sowing millet parent plants in conditions of unstable humidity of Right-Bank Forest Steppe of Ukraine for 2009-2011 on the experimental field of Uman National University of Horticulture three-factor field experiment was carried out which involved studying the mutual influence of varietal characteristics (Factor A), term (Factor B) and sowing method (Factor C) on sowing qualities and yielding properties of millet seeds. Recording, analysis and monitoring were carried out according to conventional methods. As a result of studies it was found that the field germination of seeds of millet varieties in typical for the region years with lengthening sowing time increases from early to late ones and excessive moisture conditions do not significantly reduce its level. On approaching the optimum temperature regime of air and soil conditions of germination of millet seed material are improved and its field similarity increases. Field germination of seeds is approximated by 43% with soil temperature at a depth of 10 cm and by 57% with air temperature during sowing-shoots. The greatest preservation of plants in seed coenoses of both millet varieties late spring sowing provides. In years of excessive moisture during the generative period of development most summer crops are thinned out.